The emergence of the Hebrew Christian movement in nineteenth-century Britain - Darby, Michael R., 1946- (Numen Book Series, 2010)
In nineteenth-century Britain the majority of Jewish believers in Christ worshipped in Gentile churches. Some attained ethnic and institutional independence. A few debated the implications of incorporating into their worship the observance of Jewish tradition, and advocated the theological and liturgical independence of Hebrew Christianity, characterised by opponents as the "scandal of particularity". Previous scholarship has documented several Hebrew Christian initiatives but this monograph breaks new ground by identifying almost forthy discrete institutions as components of a century-long movement. The book analyses the major pioneers, institutions and ideologies of this movement and recounts how, through identity negotiation, hebrew Christians - and also their Gentile supporters - prepared the way for the development in the twentieth century of Messianic Judaism.